Intensity Correlation of Collimated Gaussian Beams Propagating in Biological Tissues - Baykal, Yahya (Taylor & Francis Ltd, 2021)
Intensity correlations in turbulent biological tissues are evaluated when collimated Gaussian laser beam is used. Variations of the intensity correlations in biological tissues are investigated versus the diagonal distance from the origin of the observation plane for various tissue distances, biological tissue types, strength coefficients of the refractive-index fluctuations, starting points at the observation plane. Also, intensity correlations in biological tissues for various biological tissue types versus the strength coefficient of the refractive-index fluctuations, small length-scale factor, fractal dimension. It is found that intensity correlations become smaller at larger diagonal distance, tissue distance, strength coefficients of the refractive-index fluctuations, and at smaller source size, small length-scale factor and fractal dimensions. Behaviour of the intensity correlations is found to depend on the type of the biological tissue. Our results can be used in tissue identification and to find the disorders in biological tissues.
Intensity correlation of collimated Gaussian beams propagating in biological tissues
Baykal, Yahya/0000-0002-4897-0474
Keywords: Intensity Correlations; Biological Tissue Turbulence; Collimated Gaussian Laser Beams